Advancing the Discourse on Travel Writing - Venkovits, Balázs (Hungarian Journal of English and American Studies, 2020)
Book review: Kuehn, Julia, and Paul Smethurst, eds. New Directions in Travel Writing Studies. New York: Palgrave Macmillan, 2015. 325 pages. ISBN 978 1 137 45757 8. Hb. 90.